Coupling and Decoupling of Diverse Molecular Units in Glycosciences (Springer International Publishing, 2018)
This unique book covers the latest developments in coupling and decoupling of biomolecules containing functionalized carbohydrate components, being one of the first collections in this important area of applied medicinal chemistry. Connecting molecules, often referred as bio-conjugation, has become one of the most often performed procedures in modern medicinal chemistry. Sometimes, when the connected molecules are not useful anymore, they must be disconnected. The molecules that must be connected (coupled) may belong to both small and large molecules and include such constructs as glycoproteins, glycopeptides and glycans. In this work, more than 15 experts address a comprehensive range of potential and current uses of in vitro and in vivo bio-conjugation methodologies, leading to a variety of glycoconjugates. The analytical aspects of bio-conjugation are also here discussed. Medicinal and organic chemists from graduate level onwards will understand the appeal of this important book.